Emission trading systems and the optimal technology mix - Zöttl, Gregor (SERIEs : Journal of the Spanish Economic Association, 2021)
Cap and trade mechanisms enjoy increasing importance in environmental legislations worldwide. One of the important aspects of designing cap and trade mechanisms is the possibility of authorities to grant emission permits for free. Unlike analyzed in the seminal contributions on cap and trade systems, in reality free allocations are not made lump sum, but are updated contingent on firms' actions, i.e., contingent on production decisions and contingent on facilities entering the market or retiring (see IEA, https://www.oecd-ilibrary.org/content/ publication/b7d0842b-en, 2020). As it has already been shown in the literature, such updating yields distorted production decisions of firms (see e.g., Bohringer and Lange in Eur Econ Rev 49(8):2041-2055, 2005, Mackenzie et al. in Environ Resour Econ 39(3):265-282, 2008, or Damon et al. in Rev Environ Econ Policy 13(1):23-42, 2019). The impact of updating on firms' investment and retiring decisions and the resulting technology mix has received much less attention up to now, however. It is the purpose of the present article to shed light on this aspect and to study the impact of a cap and trade mechanism not only on firms' output decisions, but also on their investment incentives in different technologies and to analyze the optimal design of emission trading systems in such an environment.
CRIS-Team WoS Importer:2021-05-28